Analisis Struktural dan Pragmatis Puisi “Doa” Karya Chairil Anwar - Nurul Hadi; Aswandikari Aswandikari; Nuriadi Syaiful; Musadat Musadat; Johan Mahyudi (SENTRI: Jurnal Riset Ilmiah, 2025)
Poetry is a form of literary work rich in meaning, symbolism, and aesthetics. One prominent example that embodies the power of poetic expression is “Doa” (“Prayer”) by Chairil Anwar. This poem not only presents a deeply personal spiritual longing but also reflects the existential anxiety of humanity within its socio-cultural context. This study aims to analyze “Doa” using structural and pragmatic approaches to gain a comprehensive understanding of its meaning and function. The research employs a qualitative method based on literature review, focusing on textual analysis and relevant scholarly sources. Structurally, the poem is composed of simple yet powerful diction, religious imagery, and a style rich in symbolism and emotion. The central theme revolves around the search for the meaning of life and submission to God. Meanwhile, the pragmatic approach reveals how the poem evokes reflective and spiritual effects on its readers, demonstrating its interpretive flexibility across different social and emotional backgrounds. Therefore, “Doa” is a poem that is not only aesthetically beautiful but also spiritually and socially relevant across generations.